Convexity of Solutions for an Iterative Equation in Banach Spaces - Xiaobing Gong (Abstract and Applied Analysis)
By applying Schauder's fixed point theorem we investigate the existence of increasing (decreasing) solutions of the iterative equation and further give conditions under which those solutions are convex or concave. As corollaries we obtain results on iterative equation